Modification of Aggregate Gradation for Simultaneous Optimization of Evaporation and Permeability of Porous Asphalt Mixtures - Ghafori fard, Zohreh; Khabiri, Mohamad Mehdi; Kornél Tamás, Almássy (Frontiers in Built Environment, 2022)
Today, with the expansion of cities and the growth of urbanization, followed by climate change, it is crucial to prevent the occurrence of floods and control it in cities. Porous pavement, including porous asphalt, is known as one of the best methods for urban flood control due to its two properties of evaporation and permeability. The purpose of this study is to modify the gradation of porous asphalt in order to optimize its permeability and evaporation for low-traffic urban passages. For this purpose, permeability, evaporation and Cantabro tests were performed on samples with different gradation and percentage of bitumen; Then, using Design Expert software, the gradation and percentage of optimal bitumen were determined. Finally, the performance of asphalt gradation and optimal bitumen percentage were evaluated by performing empty space percentage, modified Latman, Marshall and psychological strength tests and Cantabro tests. The results show that with finer gradation, the permeability, evaporation and minimum bitumen percentage are reduced by about 55%, 82% and 60%, respectively. Also, the gradation is medium with 4% bitumen gradation and the percentage of bitumen is optimal, which has a good performance in low-traffic urban passages.